Curva de enfriamiento de los peloides españoles - Propiedades térmicas - Armijo Castro, Francisco; Armijo Suarez, Onica (Anales de Hidrología Médica, 2007)
Heat application is one of the most important therapeutic uses of peloids. The rational use of these products, free of century’s empirical approach, must be based on the study of their thermal properties. This paper studies the calorific capacity, the conductivity and thermal retention and the heat yield graphic of five peloids.